Economic evaluation of interventions - Miller, T.; Hendrie, Delia (Springer, 2012)
This chapter provides an introduction to the economic evaluation of injury prevention and control programs and its relevance to decision making. It explains the purpose of economic evaluation. Next, it describes the different types of economic evaluation and the measurement of costs and outcomes. It provides guidance on injury-related benefits valuation, computation of the economic analysis measures, and reporting of an economic analysis. Finally, it discusses the interpretation of economic analysis findings and the integration of economic analysis into the broader decision-making process.